IDENTITAS DIRI PADA NAMA-NAMA RUMAH MAKAN DI KOTA PONTIANAK - Wahyu Damayanti (Balai Bahasa Kalimantan Barat, 2019)
Culinary business is increasingly in demand by most culinary connoisseurs. One way for culinary entrepreneurs so that their culinary business is better known is by giving a unique name so that culinary connoisseurs are curious to visit it. Giving a name is an effort to find out the cultural value of the community owner. The purpose of this study is to describe the form of self-identity in the names of restaurants in Pontianak. The theory used uses qualitative methods. The supporting techniques are (1) determining the location of the study, (2) determining the informant technique using purposive sampling techniques developed using snowball sampling techniques. (3) data collection techniques that include observation, interviews, document studies or literature studies, (4) data validation, (5) data analysis, and finally (6) writing of research results. The results of this study are that there is a form of self-identity in many ethnic groups in Indonesia including Padang, Java, Malay, Palembang and from foreign countries such as Arabic, English, Thai, Italian, and Japanese.